2021
DOI: 10.1002/onco.13749
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Community Education and Disparities in Diagnosis and Treatment

Abstract: Prostate cancer remains the leading diagnosed cancer and the second leading cause of death among American men. Despite improvements in screening modalities, diagnostics, and treatment, disparities exists among Black men in this country. This primary objective of this systematic review is to describe the reported disparities in screening, diagnostics and treatments as well as efforts to alleviate these disparities though community and educational outreach efforts. Critical review took place of retrospective, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 140 publications
(170 reference statements)
0
10
0
1
Order By: Relevance
“…Even for the National Cancer Institute’s (NCI) clinical trials, less than 2% had a focus on the racial/minority population as their primary emphasis [ 28 ]. Other interventions include incorporating enhanced models of patient navigation, and community partnership may be beneficial to overcome this minority accrual disparity [ 32 ]. Strategies such as video-based education have also been effective in the clinical trial setting for improving enrollment of minorities [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even for the National Cancer Institute’s (NCI) clinical trials, less than 2% had a focus on the racial/minority population as their primary emphasis [ 28 ]. Other interventions include incorporating enhanced models of patient navigation, and community partnership may be beneficial to overcome this minority accrual disparity [ 32 ]. Strategies such as video-based education have also been effective in the clinical trial setting for improving enrollment of minorities [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors do not report the uptake of the invitation across different parts of the community. However, current data shows that black men, who are at increased risk of prostate cancer, may be less likely to take up an invitation for prostate cancer screening 8 . A combination of interventions may be appropriate to increase uptake 9 , and the potential increase in acceptability in removing the need for digital rectal examination seems likely to contribute to a willingness to be screened across many communities.…”
mentioning
confidence: 87%
“…For instance, studies conducted in the United States have identified factors such as access to Medicare (a national health insurance program) and private health insurance status, trial inclusion, and educational level as major barriers to prostate cancer screening. 39,44,45 In addition, individuals currently incarcerated are likely to experience discrimination in using the health care system and unequal access to cancer screening. 46 Because of the diverse nature of the UK population, factors such as low health literacy, culture, language, low screening uptake in individuals with mental illness, and low income have been identified as the major Cancer August 1, 2022 barriers to cancer screening.…”
Section: Disparities In Prostate Cancer Screening and Diagnosismentioning
confidence: 99%
“…However, several factors why men at high risk of developing prostate cancer are not being identified for treatment also come into play. For instance, studies conducted in the United States have identified factors such as access to Medicare (a national health insurance program) and private health insurance status, trial inclusion, and educational level as major barriers to prostate cancer screening 39,44,45 . In addition, individuals currently incarcerated are likely to experience discrimination in using the health care system and unequal access to cancer screening 46 .…”
Section: Disparities In Prostate Cancer Screening and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation